Comparative Analysis of Fecal Bacterial Microbiota of Six Bird Species - Gao, Li; Liu, Li; Du, Chao; Hou, Qiangchuan (Frontiers in Veterinary Science, 2021)
The gut microbiota contributes to host health by maintaining homeostasis and improving digestive efficiency. Therefore, identifying gut microbes will shed light on the annual life cycle of animals and in particular those that are threatened or endangered. Nonetheless, the gut microbial composition of the majority of bird species is still unknown. Here, for the first time, 16S rRNA gene sequencing was used to characterize and compare the community composition and diversity of gut microbiotas from six species of birds raised at the Wildlife Conservation Center in Baotou, China: relict gull (Larus relictus; n = 3), muscovy duck (Cairina moschata; n = 3), ruddy shelduck (Tadorna ferruginea; n = 3), demoiselle crane (Anthropoides virgo; n = 4), whooper swan (Cygnus cygnus; n = 3), and black swan (Cygnus atratus; n = 5). A total of 26,616 operational taxonomic units from 21 samples were classified into 32 phyla and 507 genera. Chao1, Shannon diversity, observed species, and Simpson index analysis revealed differences in the community richness and diversity between the different species. Proteobacteria was the dominant bacterial phylum in whooper swan and relict gull, whereas Firmicutes was the dominant bacterial phylum in the other species. At the genus level, 11 dominant genera were detected (Lactobacillus, Psychrobacter, Enterococcus, Carnobacterium, Weissella, Burkholderia, Escherichia/Shigella, Leuconostoc, Buttiauxella, Desemzia, and Staphylococcus). Principal component and cluster analyses revealed that, while the microbial community composition of different individuals of the same species clustered together, the gut microbial composition varied between the bird species. Furthermore, the most abundant bacterial species differed between bird species. Because many avian gut microbes are derived from the diet, the eating habits and natural living environment of birds may be important contributing factors to the observed differences. Short-term changes to the diet and living environment have little effect on the composition of the avian gut microbiota. This study provides a theoretical basis for bird protection, including disease prevention and control.